Comparison of Botryosphaeran production by the ascomyceteous fungus Botryosphaeria sp., grown on different carbohydrate carbon sources, and their partial structural features - Steluti, R. M.; Giese, E. C.; Piggato, M. M.; Sumiya, AFG; Covizzi, L. G.; Job, A. E.; Cardoso, M. S.; Da Silva, M. D.; Dekker, RFH; Barbosa, A. M. (Wiley-Blackwell, 2004)
The influence of glucose concentration and other carbohydrates (monosaccharides: fructose, galactose, mannose; polyols: mannitol and sorbitol; disaccharides: lactose, sucrose and commercial sucrose; and industrial sugarcane molasses) were compared as sole carbon sources for the production of Botryosphaeran, an exopolysaccharide (EPS) produced by Botryosphaeria sp. The optimum glucose concentration for EPS production was 50 g 1(-1). With the exception of mannitol, the fungus produced EPS on all carbon sources studied, with highest yields occurring with sucrose followed by glucose. All EPS showed exclusively glucose after acid hydrolysis and monosaccharide analysis. FTIR spectroscopy demonstrated the presence of beta-anomers indicating that all the EPS produced by Botryosphaeria sp. on the different carbon sources were essentially of the beta-D-glucan type.